Does leaving welfare improve health? Evidence for Germany - Martin Huber; Michael Lechner; Conny Wunsch (Institute for the Study of Labor (IZA), 2009)
Using exceptionally rich linked administrative and survey information on German welfare recipients we investigate the health effects of transitions from welfare to employment and of assignments to welfare-to-work programmes. Applying semi-parametric propensity score matching estimators we find that employment substantially increases (mental) health. The positive effects are mainly driven by males and individuals with bad initial health conditions and are largest for males with poor health. In contrast, the effects of welfare-to-work programmes, including subsidized jobs, are ambiguous and statistically insignificant for most outcomes. Robustness checks that include a semi-parametric instrumental variable approach do not provide reasons for concern.
Keywords: I38; J68; I10; 330; Welfare programs; health effects; Gesundheit; Arbeitslosigkeit; Berufliche Integration; Aktivierende Sozialhilfe; Beschäftigungseffekt; Deutschland